Respuesta :
Given:
The expression: (1 + x)^n
The Binomial Theorem is used to predict the products of a binomial raised to a certain power, n, without multiplying the terms one by one.
The following formula is used:
(a + b)^n = nCk * a^(n-k) * b^k
we have (1 +x)^n,
where a = 1
b = x
let n = 4
First term, k = 1
4C1 = 4
first term: 4*(1^(4-1))*x^1
Therefore, the first term is 4x. Do the same for the next three terms.
2nd term: k =2
3rd term: k = 3
4th term: k = 4
The expression: (1 + x)^n
The Binomial Theorem is used to predict the products of a binomial raised to a certain power, n, without multiplying the terms one by one.
The following formula is used:
(a + b)^n = nCk * a^(n-k) * b^k
we have (1 +x)^n,
where a = 1
b = x
let n = 4
First term, k = 1
4C1 = 4
first term: 4*(1^(4-1))*x^1
Therefore, the first term is 4x. Do the same for the next three terms.
2nd term: k =2
3rd term: k = 3
4th term: k = 4
Answer:
part A answer below.. Sorry, I don't know the part B
Step-by-step explanation:
1st term C(n,0) [tex]1^nx^0[/tex] = [tex]\frac{n!}{(n-0)! (0!)}[/tex] [tex]1^nx^0[/tex] = 1 ·1 ·1 = 1
2nd term C(n,1) [tex]1^n^-^1x^1[/tex] = [tex]\frac{n!}{(n-1)!(1!)}[/tex] [tex]1^n^-^1x^1[/tex] = [tex]\frac{n!}{(n-1)!}x[/tex]
3rd term C(n,2) [tex]1^n^-^2x^2[/tex] = [tex]\frac{n!}{(n-2)!(2!)} 1^n^-^2x^2[/tex] = [tex]\frac{n!}{2(n-2)!}x^2[/tex]
4th term C(n,3)[tex]1^n^-^3x^3[/tex] = [tex]\frac{n!}{(n-3)!(3)!} 1^n^-^3x^3[/tex] = [tex]\frac{n!}{6(n-3)!} x^3[/tex]